2009
DOI: 10.1099/vir.0.013227-0
|View full text |Cite
|
Sign up to set email alerts
|

Transmissions of variant Creutzfeldt–Jakob disease from brain and lymphoreticular tissue show uniform and conserved bovine spongiform encephalopathy-related phenotypic properties on primary and secondary passage in wild-type mice

Abstract: Prion strains are defined by their biological properties after transmission to wild-type mice, specifically by their incubation periods and patterns of vacuolar pathology (‘lesion profiles’). Preliminary results from transmissions of variant Creutzfeldt–Jakob disease (vCJD) to wild-type mice provided the first compelling evidence for the close similarity of the vCJD agent to the agent causing bovine spongiform encephalopathy (BSE). Complete results from this investigation, including the transmission characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
35
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 33 publications
16
35
0
3
Order By: Relevance
“…Secondly, we have shown that prions associated with distinct PrP Sc glycotypes in vCJD brain (type 4) [2] or lymphoreticular tissues (type 4t) [33,34] do not transmit disease with distinct prion strain properties. These findings are in agreement with two other recent studies that have also shown congruent prion strain properties after transmission of brain or lymphoid tissue from sheep scrapie to bank voles [67] or from vCJD to wild-type mice [68]. Prion strains may comprise an ensemble or quasispecies maintained under selection pressure in a host and the populations of which may therefore differ in different tissues [52,69].…”
Section: Discussionsupporting
confidence: 92%
“…Secondly, we have shown that prions associated with distinct PrP Sc glycotypes in vCJD brain (type 4) [2] or lymphoreticular tissues (type 4t) [33,34] do not transmit disease with distinct prion strain properties. These findings are in agreement with two other recent studies that have also shown congruent prion strain properties after transmission of brain or lymphoid tissue from sheep scrapie to bank voles [67] or from vCJD to wild-type mice [68]. Prion strains may comprise an ensemble or quasispecies maintained under selection pressure in a host and the populations of which may therefore differ in different tissues [52,69].…”
Section: Discussionsupporting
confidence: 92%
“…In this study both CNS and peripheral material was transmitted and showed that in all cases transmission characteristics were similar to BSE. 12 To date, all cases of UK 129MM (methionine homozygous) vCJD that have been characterized have shown similar strain characteristics to BSE.…”
Section: 11mentioning
confidence: 99%
“…14 This BSE/vCJD PrP res type (referred to a type 2B or type 4) appears to be closely associated with the agent since (1) it also characterizes the PrP res that accumulates in peripheral tissues in clinical vCJD, 16 (2) it is maintained following secondary transmission of vCJD by blood transfusion both in the brain of clinical cases, 17 and in the spleen of asymptomatic or preclinical individuals, 18,19 (3) it is largely stable on transmission to wild-type and humanised transgenic mice 12,20 and (4) it is maintained in cell-free conversion systems in which either BSE or vCJD brain homogenates are used to seed conversion of normal human prion protein. 21 While type 2B PrP res provides a convenient additional diagnostic tool for human BSE identification, 22 it does not provide a complete description of PrP Sc in cases of vCJD, nor does it provide a biochemical definition of the agent.…”
Section: 11mentioning
confidence: 99%
“…38 It is now understood that vCJD reflects the transmission of BSE to humans via the consumption of infected beef. 13,[39][40][41][42][43] BSE AND VCJD IN BRITAIN, 1984BRITAIN, -1996 The origins of the BSE crisis in Britain have been traced to Sussex in December 1984, when a cow fell ill with a new clinical syndrome: tremor and incoordination rapidly leading to death. Within a few months, cows from all across Britain had succumbed to a similar constellation of symptoms.…”
Section: The Science Of Bsementioning
confidence: 99%